PyMIF enhances the inflammatory response in a rodent model by stimulating CD11b+Ly6C+ cells accumulation in spleen. (June 2016) - Liu, J.; Shao, D.; Lin, Y.; Luo, M.; Wang, Z.; Yao, M.; Hao, X.; Wei, C.; Gao, Y.; Deng, W.; Wang, H.
Summary: Macrophage migration inhibitory factor (PMIF) expressed by Plasmodium parasites has been proved to be similar to the mammalian MIF in both structure and biological activity and is a critical upstream regulator in antimalaria innate immunity. In this work, using a genetically modified (MIF‐KO) strain of highly lethal rodent Plasmodium yoelii 17XL (Py17XL), we found that PyMIF could increase the secretion of pro‐inflammatory factors by eliciting the CD11b + Ly6C + cells accumulated in the spleen of infected mouse. In addition, the chemotactic effect of PyMIF was demonstrated to associate with cell receptors CXCR2, CXCR4 and the cell surface markers ICAM‐1, LFA‐4.